ANALISIS KEMAMPUAN LITERASI MEMBACA PADA CERITA LEGENDA SISWA KELAS 5 DI SDN CIPONDOH 8 KOTA TANGERANG - Zulfah Hilmiyah; Ino Budiatman; Yayah Huliatunisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT Reading literacy is a core part of learning is schools that cannot be separated. This ability is the most basic foundation for achieving success in learning. The purpose of this study was to describe the literacy skills in reading comprehension of legend stories for fifth grade students at SDN Cipondoh 8, Tangerang City. The focus of this study was to determine the extent of literacy skills in reading comprehension of ledend stories for fifth grade students at SDN Cipondoh 8 Tangerang City. This research is a descriptive qualitative study with a teacher as the subject and 26 fifth grade students. The data collection techniques used were tests, interview, observation, and documentation. The research method used is descriptive method and data analysis uses data triangulation which consists of three activities namely, data reduction, data presentation and conclusions. Of the 26 subjects who were given a test to answer story questions, 2 people got grades in the very good category, then 10 people got grades in the good category, and 14 people got scores in the fair category. The results of the study showed that almost all students reading comprehension literacy skills were quite good, based on students comprehension abilities on indicators of understanding the meaning of words and the meaning of the stories they read.